2017
DOI: 10.1016/j.jcte.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Coherence is associated with LDL-cholesterol in patients with type 1 diabetes – The PROLONG-Steno study

Abstract: HighlightsSOC was compared to clinical biomarkers in 125 people with type 1 diabetes.No association between SOC and HbA1c was found.An independent association between high SOC and lower LDL-C was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
0
7
0
5
Order By: Relevance
“…Only one study referred to a positive and significant correlation between SOC and A1c 44 . Other studies reported no association between SOC and biomarkers such as: A1c 23,26,27 , triglyceride levels 23 , BMI 21,24 , HDL cholesterol 23,24 , SBP 23 and DBP 23 (Table 3).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Only one study referred to a positive and significant correlation between SOC and A1c 44 . Other studies reported no association between SOC and biomarkers such as: A1c 23,26,27 , triglyceride levels 23 , BMI 21,24 , HDL cholesterol 23,24 , SBP 23 and DBP 23 (Table 3).…”
Section: Resultsmentioning
confidence: 94%
“…The results in the category of disease control were diverse. Some authors claim that there is a negative and significant correlation between SOC and the biomarkers, which suggests that people with a strong SOC will have lower triglyceride 24 , A1c 21,22,24,41 , LDL cholesterol 23 and BMI 22 levels. On the other hand, two studies suggest an indirect association between SOC and A1c, and that this relationship is mediated by health self-assessment 42 , AC, and psychopathological symptoms 43 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations